A Bibliometric Study of the Journal Tropical Veterinarian 2000-2009 - Hundu, Jacob; Anaele, Ijeoma Onyeka (MiddleBelt Journal of Library and Information Science, 2014)
The objective of the study was to make a bibliographic and citation analysis of articles published in the journal Tropical Veterinarian from 2000 – 2009. The methodology applied in the study is bibliometric analysis, which is used to study in detail the bibliographic features of the articles and citation analysis of the references at the end of each article published in Tropical Veterinarian from 2000-2009. The study shows that 229 articles were published in the ten volumes-20 (2000) to 29(2009) studied. The study revealed that maximum number of contributions comes from joint authors with 88.2%. Also, most of the articles (64.4%) contain references which include journals.